Synthesis and Biological Activity of 7-Benzyloxy and 7-Methoxy Flavone (Biological Sciences - PJSIR, 2007)
. Benzyl and methyl d erivatives of 7-hydroxyflavone were synth esized from 2-hyd roxy-4 -benzyloxy acetophenon e and 2-hydroxy -4-methoxyacetophenone, respectivel y, via chal cone precu rsor and by the treatment with DMS0/ 12 , diphenyl sul ph ide and d ichloro d icyan o qu i n on e (DDQ). The an t i bacteri al and antifunga l activ i tyof these flavones and thei r  correspond i ng chalcones were  fou nd  in  vitro by the  fi l ter  paper d i sc diffu si on methodand poi son ed food techn iq ue .